MODEL PENGELOLAAN LINGKUNGAN DI KAWASAN PARIWISATA NUSA PENIDA, BALI - Sudipa, Nyoman; Sudiana Mahendra, Made; Sandi Adnyana, Wayan; Pujaastawa, Ida Bagus (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2020)
As a regional income barn, the Nusa Penida Tourism Area needs to be managed comprehensively by involving all available resources, by encouraging new thinking about managing tourism that synergizes with environmental sustainability in the sustainable environment of the Nusa Penida Tourism Area. Tourism can increase economic growth but create a burden on the environment, so that Nusa Penida tourism becomes environmentally friendly tourism to support the development of green tourism. Progress in tourism impacts the environment, causes social and cultural changes in society and impacts the carrying capacity of land and water from the massive tourism development in Nusa Penida. For this reason, it is necessary to formulate a model of environmental management that is relevant and has been developed.This study uses a systems approach with the Interpretative Structural Modeling (ISM) method to formulate an environmental management model in the Nusa Penida Tourism Area. This method can be used to help a group, in identifying contextual relationships between sub elements of each element that forms a system based on ideas / structures or determinants in a complex problem (Saxena, 1992).The environmental management model in the Nusa Penida was formed based on government initiatives by involving all stakeholders as representatives of the Nusa Penida community and involving other elements such as non-government organizations and universities. In the management of the environment, institutional arrangements that specifically handle the environment and tourism of Nusa Penida must be formed with the government as the initiator and formed in a participatory manner. The recommended model of environmental management needs to be applied carefully and continued with the formation of institutions by involving the affected community sectors in Nusa Penida's environmental management and tourism.Keywords: tourism, model, management, environment, Nusa Penida